Noninvasive Imaging of the Biliary System Relevant to Percutaneous Interventions - Thomas, Stephen; Jahangir, Kayleen (Seminars in Interventional Radiology, 2016)
Clinical data such as history, physical examination, and laboratory tests are useful in identifying patients with biliary obstruction and biliary sources of infection. However, if intervention is planned, noninvasive imaging is needed to confirm the presence, location, and extent of the disease process. Currently, the most commonly available and used noninvasive modalities are ultrasound (US), computed tomography (CT), magnetic resonance (MR), and nuclear medicine hepatobiliary scintigraphy (HIDA). US is quick, portable, readily available, and is commonly the first imaging modality used when biliary pathology is suspected. It is excellent in the detection of cholelithiasis and acute cholecystitis but is limited in detecting choledocholithiasis. CT is excellent at detecting infected postoperative fluid collections, bilomas, biliary obstruction, and biliary infection but is limited in the detection of cholelithiasis. Therefore, US may be more useful than CT for the initial screening of acute biliary disease. MR has inherent advantages over CT, as it does not use ionizing radiation, can be done without intravenous contrast, and its detection of cholelithiasis is not affected by the internal composition of the stone. Magnetic resonance cholangiopancreatography can be used to determine the cause and location of biliary obstruction but is limited in the detection of small stones and the evaluation of the biliary tract near the ampulla. HIDA is used to evaluate for cholecystitis, biliary obstruction, and bile leaks. The main limitation is its lack of anatomical detail, and it is therefore frequently performed in conjunction with other described modalities.
Keywords: cholelithiasis; cholecystitis; interventional radiology; biliary obstruction; biloma